Tissue Culture Of Hevea Brasiliensis Müll. Arg. Latex Timber Clone (Ltc) Rrim 929 - Khoo, Marisa Kim Gaik (2021)
Rubber tree or Hevea brasiliensis Müll. Arg. is a commercially important crop widely cultivated in Southeast Asia for its ability to produce natural rubber in the form of latex. This perennial crop plant is known for its recalcitrance in rooting and only limited clones could be regenerated via tissue culture. Clone that could be regenerated via tissue culture will be a promising tool for Hevea crop improvement. Many available commercial clones have yet to be tested for their potential in regenerated via tissue culture, more clones should be explored. In this study, H. brasiliensis clone RRIM 929, a latex timber clone (LTC) has been studied for in vitro propagation via embryo culture, somatic embryogenesis and microcutting from both seedling and bud-grafted plant material for the first time.